The violent land eaudiobook Family jensen series, book 3. - Johnstone, William W. (Family Jensen, 2012)
A family of Old West vigilantes helps a group of mysterious strangers in this adventure by the bestselling authors of Helltown Massacre . William W. Johnstone's legendary mountain men have fought their battles and conquered a fierce frontier. Now, three generations of the Jensen clan are trying to live in peace on their sprawling Colorado ranch. But for men with fighting in their blood, trouble is never very far from their doorstep ... Into The Eye Of A Storm They are strangers in a strange land—a band of German immigrants trespassing across the Jensen family spread. Led by a baron fleeing a dark past in Germany and accompanied by a woman beautiful enough to dazzle young Matt, the pilgrims are being pursued by a pack of brutal outlaws hungry for blood, money—or maybe something else. ... The Jensens are willing to help the pioneers get to the promised land in Wyoming. But they don't know the whole story of their newfound friends, or who the outlaws really are. By the time the wagon train reaches Wyoming the truth is ready to explode—in a clash of hard fighting, hard choices, and hard deaths in a violent land ...